The effectiveness of iot-based learning media for supporting the expertise program of renewable energy engineering in vocational high school - Kayohana, Ketut Widya; Asnawi, Rustam; Amaria, Marshanda Alfa (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
The objectives of this study are: (1) the performance of developing renewable energy based on IoT (Internet of Things) in the renewable energy engineering expertise program in the subject of solar hydro-wind energy (Tesha) engineering at Vocational Schools, (2) the level feasibility of development renewable energy based IoT in the subject Tesha's learning at Vocational Schools, (3) level effectiveness development renewable energy based IoT in the subject Tesha learning at Vocational Schools. This research is a research and development research with ADDIE approach (Analyze, Design, Develop, Implement, Evaluate) (Branch (2009) with approach experiments that will used is Quasi Experimental Design with form Nonequivalent Control Group Design. Results from study this show: (1) the feasibility of learning media